Effectiveness of The Role of the Criminal Office in using Restorative Justice to Improve the Settlement of Domestic Violence Crimes in the Jurisdiction Malang Police Region - Fachmi Ady Kurniawan; Jarot Muchtar; Muhammad Imam Farid (Tanggon Kosala, 2024)
This research aims to analyze the effectiveness of the role of the Malang Police Satreskim in using restorative justice to increase the resolution of domestic violence crimes. In this research, a qualitative approach was also used with field research methods through direct data collection from relevant agencies through interviews, observation, and documentation, as well as literature studies combined with validation techniques from data triangulation. The results of the research show that 1) the application of restorative justice in resolving domestic violence crimes in the Malang Police jurisdiction is carried out based on the Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice and the Criminal Investigation Department's Telegram Letter Number: ST/480/IV /HUK.5.1./2022 dated 20 April 2022. The application of restorative justice in resolving domestic violence crimes in the Malang Police jurisdiction was carried out through mediation efforts and succeeded in reaching an agreement between the reported party and the reporter to make peace; 2) The role of the Malang Criminal Investigation Unit in using restorative justice to improve the resolution of domestic violence crimes is still deemed to be ineffective. Malang Criminal Investigation Unit faces obstacles in communication, where many people do not understand the concept of restorative justice. The competency factor of members in implementing restorative justice in resolving domestic violence crimes is still not optimal, especially since there are still many people who do not understand the procedures and mechanisms of restorative justice in resolving domestic violence crimes.